Urban-rural exploitation: An underappreciated dimension of environmental injustice. (October 2016) - Kelly-Reif, Kaitlin; Wing, Steve
Abstract: Relationships in which populations benefit from practices that harm other populations are environmentally unjust. Environmental injustice commonly occurs due to disparities in economic and political power, and it is typically analyzed along dimensions of race and class. However, an urban-rural dimension of environmental injustice exists, one that intersects with race and class. Rural environmental injustice can be characterized as a parasitic relationship between urban and rural communities because urban populations obtain most of their food and energy from rural areas and return their wastes to rural areas. We explore the negative consequences of agricultural and energy production in rural areas through two examples: industrial hog production in eastern North Carolina and the Fukushima Daiichi nuclear disaster in Japan. The negative public health impacts of urban-rural environmental injustice come from human exposure to specific pollutants, degradation of the built environment, limits on popular democracy, and ultimately, suppression of the feedback between consumption and production that could lessen global environmental problems. Pressure to control the effects of industrial energy and agriculture systems is lessened because the urban majority does not experience environmental degradation that affects rural populations. A basic step towards reducing rural environmental injustice is to develop the scientific framework needed to monitor pollutants and health outcomes in rural places through partnerships between researchers and rural community members that promote broader goals of economic, racial and social justice. Highlights: Aspects of rural environmental injustice can be viewed as a form of urban parasitism. Industrialized food and energy production promote rural environmental injustice. Rural environmental injustice is compounded by racism, classism, and imperialism. Researchers can partner with rural communities to oppose environmental injustice.